A risk stratification approach to assessing for true cases of measles in a highly vaccinated population. (15th May 2016) - Bond, Katherine; Martin‐Gall, Veronica; Franklin, Lucinda; Sutton, Brett
Abstract: Objective : In Australia, the notification rate for measles fluctuates greatly between baseline and outbreak periods. We aimed to identify characteristics of notified cases that allow risk stratification in order to improve the efficiency of the public health response in an outbreak setting. Methods : Retrospective descriptive case series for all measles notifications made to the Victorian Government Department of Health between 1 August and 30 September 2013. Results : A total of 151 notifications were included in the analyses, of which 17 (11%) were confirmed as measles. Applying the clinical criteria of the measles case definition or identifying susceptible cases (determined by vaccination status) correctly identified all measles cases. Requiring cases to meet both criteria reduced sensitivity to 88%, but improved the positive predictive value (48% vs 25%) and retained a high negative predictive value (98.33%). Application of a risk stratification approach based on these features would have saved intensive public health follow‐up for 79.5% of notifications in this outbreak. Conclusions : Immune status and clinical features can reliably be used to predict which notifications are unlikely to become confirmed cases. Implications : Risk stratification and modification of current surveillance practices may provide for a more efficient public health response, particularly during periods of increased case notification.